2017
DOI: 10.1080/10717544.2017.1309476
|View full text |Cite
|
Sign up to set email alerts
|

Electrosteric stealth Rivastigmine loaded liposomes for brain targeting: preparation, characterization, ex vivo, bio-distribution and in vivo pharmacokinetic studies

Abstract: Being one of the highly effective drugs in treatment of Alzheimer's disease, Rivastigmine brain targeting is highly demandable, therefore liposomal dispersion of Rivastigmine was prepared containing 2 mol% PEG-DSPE added to Lecithin, Didecyldimethyl ammonium bromide (DDAB), Tween 80 in 1:0.02:0.25 molar ratio. A major challenge during the preparation of liposomes is maintaining a stable formulation, therefore the aim of our study was to increase liposomal stability by addition of DDAB to give an electrostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Nonetheless, it was reported that rivastigmine hydrogen tartrate undergoes an extensive first-pass effect in the liver, which decreases bioavailability [ 10 , 11 ]. This molecule also has a short half-life and a hydrophilic nature, which makes it difficult for it to pass through the blood brain barrier (BBB) and cerebrospinal fluid (CSF) [ 5 , 9 , 12 ]. In addition, the tight junctions between the BBB capillary endothelial cells restrict the passage, absorption, and permeation of drugs to the brain [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it was reported that rivastigmine hydrogen tartrate undergoes an extensive first-pass effect in the liver, which decreases bioavailability [ 10 , 11 ]. This molecule also has a short half-life and a hydrophilic nature, which makes it difficult for it to pass through the blood brain barrier (BBB) and cerebrospinal fluid (CSF) [ 5 , 9 , 12 ]. In addition, the tight junctions between the BBB capillary endothelial cells restrict the passage, absorption, and permeation of drugs to the brain [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their surface can be easily modified to provide them with multiple functions [17]. This has already been demonstrated for improvement of intranasal delivery [18] of rivastigmine [19,20], donepezil [21], zolmitriptan [22].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of rivastigmine,, its synthesis has been studied widely in organic chemistry . Over the past three decades, several strategies for the synthesis of rivastigmine have been developed.…”
Section: Introductionmentioning
confidence: 99%